Physiological and Psychological Impacts of Shift Work Among Student Pharmacists: Sex Differences in Stress and Health Outcomes - Mohammed F. Salahuddin; Richard Bugingo; Fakhri Mahdi; Delilah Spencer; Md Dilshad Manzar; Jason J. Paris (Psychiatry International, 2025)
Shift work is prevalent among healthcare professionals and associated with significant health risks, including stress, sleep disturbances, and mood disorders. Despite known sex differences in stress responses, their impact on shift workers, particularly student pharmacists, is understudied. The objective of this study was to explore sex-specific differences in psychological and physiological stress responses among pharmacy students engaged in shift work. Psychological stress was assessed using validated scales like the Perceived Stress Scale (PSS), Shift Work Disorder Index (SWDI), Ford Insomnia Response to Stress Test (FIRST), and Positive and Negative Affect Schedule (PANAS). Additionally physiological stress was assessed using salivary biomarkers like cortisol, DHEA-S, IL-6, and alpha-amylase. Females reported significantly higher perceived stress (p = 0.0004), SWDI (p = 0.0302), insomnia (p = 0.0111), and negative affect (p = 0.0171) compared to males. Rotating shift workers showed elevated scores across all measures (p = 0.0005–0.0381). Female rotating shift workers exhibited higher alpha-amylases (p = 0.0191) and lower DHEA-S levels (p = 0.0176) than males. Strong correlations emerged between perceived stress and insomnia (r = 0.40, p = 0.0001) and between insomnia and negative affect (r = 0.55, p < 0.0001). Findings highlight females’ vulnerability, underscoring the need for sex-specific interventions and the early identification of stress biomarkers.